Determination of pore size distribution in soybean seed coats by mercury porosimetry - La Scala, N.; Florentino, A. O.; Carvalho, N. M. (Ista, 1999)
In this work we applied mercury porosimetry for the investigation of soybean seed coats. By using this method it was possible to determine the pore size distribution and also the pore size dispersion that is present in seed coats. The results showed that for the studied soybean genotype the seed coats had a characteristic pore diameter, but deviation of this size was not negligible. Finally, the results were confirmed by electron microscopy.